2011
DOI: 10.1247/csf.10008
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Cancer Cell Repopulation: A Possible Mechanism Implied by Experiments Using Transplantable Mouse-derived Sarcoma Cell Line

Abstract: ABSTRACT. Purpose: Treatment with any cytotoxic agent can trigger surviving cells in a tumor to divide faster than before. This phenomenon is widely recognized as "repopulation". To better clarify the mechanism, gene expression profiling and pathological experiments were performed. Materials and Methods: A mouse fibrosarcoma cell line, QRsP, was used. Cells were irradiated with 10 Gy. Colony assay and cloning were performed. Six clones were established. cDNA analysis was performed on the clone that showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Cancer cells that survive after irradiation acquire malignant phenotypes [25]. We previously reported that P cells that survive after irradiation (IR cells) are more invasive than non-irradiated P cells [68].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells that survive after irradiation acquire malignant phenotypes [25]. We previously reported that P cells that survive after irradiation (IR cells) are more invasive than non-irradiated P cells [68].…”
Section: Resultsmentioning
confidence: 99%
“…However, some cancer cells survive after irradiation and repopulate tumors with highly malignant phenotypes, such as high proliferative ability and invasiveness, which correlate with poor prognosis [25]. As shown in our previous studies, lung cancer cells that survive irradiation acquire invasive ability that is dependent on cell-matrix adhesion regulated by integrin β1, cellular contractile force modulated by myosin regulatory light chain (MRLC), and molecular signaling mediated by epidermal growth factor receptor and other molecules [68].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cell repopulation is a key process causing tumor relapse during cancer chemotherapy or radiotherapy [13]. Repopulation of surviving tumor cells can occur between dose fractions of either radiation or chemotherapy and can lead to treatment failure [14].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis Factor-α (TNF-α) also stimulates LOX expression (Voloshenyuk et al, 2011b). It is interesting that our irradiation-surviving cells expressed higher IL6-(36.0-fold) and LOX-mRNA (4.8-fold) compared to un-irradiated parental cells in vitro (Nishioka et al, 2011). IL6 might have an influence on LOX expression.…”
Section: Introduction and Molecular Biology Of Loxmentioning
confidence: 90%